Proposing preoperative neutrophil percentage-to-albumin ratio as an effective prognostic factor for postoperative prognosis of distal cholangiocarcinoma: a retrospective cohort study - Wang, Han-xuan; Wang, Zu-yu; Lyu, Shao-cheng; Huang, Jin-can; He, Qiang; Lang, Ren; Jiang, Tao (Frontiers in Medicine, 2026)
BackgroundThe neutrophil percentage-to-albumin ratio (NPAR) is a novel inflammatory-nutritional biomarker that has prognostic value in various cancers. This study aimed to evaluate the predictive value of preoperative NPAR for postoperative prognosis in patients with distal cholangiocarcinoma (dCCA).MethodsWe retrospectively analyzed dCCA patients who underwent radical surgery between January 2011 and December 2023. Independent risk factors were identified using univariate and multivariate analysis. The prognostic performance of NPAR was assessed using receiver operating characteristic (ROC) curve analysis, and the optimal cutoff value was determined. Survival outcomes were compared using the log-rank test, and propensity score matching (PSM) was applied to adjust for confounders. Predictive models were developed using multiple machine-learning algorithms.ResultsAmong 192 included patients, NPAR demonstrated an area under the ROC curve of 0.702 inpredicting postoperative survival, with an optimal cutoff value of 1.735. Multivariate analysis confirmed that elevated preoperative NPAR was an independent risk factor for both disease-free survival (DFS) and overall survival (OS). Patients with NPAR > 1.735 had significantly worse postoperative outcomes. Subgroup analysis indicated that NPAR had stronger predictive value in patients with tumor invasion depth > 12 mm, but without portal vein invasion or lymph node metastasis. Machine-learning models incorporating NPAR improved the prediction of postoperative prognosis in dCCA.ConclusionElevated preoperative NPAR (>1.735) is an independent risk factor for postoperative DFS and OS in dCCA patients and may serve as a potential prognostic index.